Enhancing digital technology graduates' employability in the fourth industrial revolution from employers' perspective - Ling Chai Wong; Ying Ying Tiong; Poh Kiong Tee; Bee Lian Song; Nor Azrul Mohd Zin; Siao Fui Wong (PaperASIA, 2025)
The Fourth Industrial Revolution has resulted in a significant digital skill gap between employees' current skills and job demand, requiring new skills to correspond with technological changes. Unfortunately, there is a scarcity of studies that address both direct and indirect indicators in the employability of digital technology graduates, particularly in Malaysia. The objective of the study is to forecast the indicators of employability, such as industry specific knowledge, digital skills, and the mediating effect of professional network and adaptability of digital technology graduates. In terms of methodology, the current study employed the purposive sampling method to collect data from 180 respondents throughout Malaysia, and PLS-SEM 4.0 was used to analyze data. The results show that human skill that encompasses industry-specific knowledge and Digital Skills into the higher education system are critical for improving the employability of Digital Technology Graduates in the Fourth Industrial Revolution. However, from the perspective of employers, both professional network and adaptability, which represent the competitive advantages, were found to be insignificant in terms of digital technology graduates' employability. Furthermore, the current study discovered that only professional networks had a mediating effect on both industry-specific knowledge, digital skills, and the employability of digital technology graduates. The current study concludes that both digital skills and industry-specific knowledge have a significant impact on digital technology graduates' employability in the fourth industrial revolution from the employers' perspective. This is followed with the final section of this study, which includes recommendations for future research.